Effect of extending the time after bronchodilator administration on identifying bronchodilator responsiveness in a pediatric pulmonary clinic. Issue 8 (3rd July 2017) - Cogen, Jonathan D.; DiBlasi, Robert M.; Gibson, Ronald L.; Debley, Jason S.
Abstract: Objectives: American Thoracic Society/European Respiratory Society (ATS/ERS) spirometry interpretation guidelines recommend ≥15 min between pre‐ and post‐bronchodilator testing to evaluate for a bronchodilator response. We aimed to lengthen the time between albuterol administration and post‐bronchodilator testing to adhere to ATS/ERS guidelines and evaluated if lengthening this wait time would increase the percentage of patients classified as bronchodilator responsive. Methods: We compared the proportion of patients with a positive bronchodilator response between two groups of children with asthma, one group in which post‐bronchodilator administration wait times were not standardized (pre‐intervention) to another in which the wait time was extended to 15 min to adhere to ATS/ERS standards (post‐intervention). We also determined the effect of this intervention on clinic appointment duration. Results: The analysis included 271 patients (145 pre‐intervention and 126 post‐intervention). The average wait time in the pre‐intervention group was 6.5 ± 2.1 (mean ± SD) minutes compared to 16.2 ± 3.2 min ( P < 0.001) post intervention, and clinic times increased from 83.0 ± 29.6 min to 91.7 ±22.5 min ( P < 0.007) from the pre‐ to post‐intervention group, respectively. In adjusted regression analysis, there was no significant change in FEV1 % predicted between the two groups. Conclusions: In a busy pediatric pulmonary clinic, while we successfully lengthened time between albuterol administration and post‐bronchodilator testing in the vast majority of patients, no difference was seen in the percentage of patients classified as bronchodilator responsive. Results from this study appear to question the ATS/ERS recommended 15 min post‐bronchodilator administration wait time for children.